PENGARUH KONFORMITAS TEMAN SEBAYA DAN INTENSITAS MENGAKSES MEDIA SOSIAL TERHADAP MINAT BELAJAR - Wahyu Aji Susanto; Itsna Iftayani; Widyaning Hapsari (PT. Hasba Edukasi Mandiri, 2026)
This study aims to analyze the effect of peer conformity and the intensity of social media use on students’ learning interest. In the context of modern education, learning interest is influenced not only by internal factors but also by social and digital environments that increasingly dominate adolescents' lives. This research employed a quantitative approach with a correlational design. The subjects were 162 high school students in Purworejo Regency, selected using accidental sampling technique. Data were collected through questionnaires measuring peer conformity, social media usage intensity, and learning interest. The data were analyzed using multiple linear regression. The results showed that peer conformity did not have a significant effect on learning interest, while the intensity of social media use had a significant effect on learning interest. Simultaneously, both variables were found to significantly influence students’ learning interest. These findings indicate that digital factors play a more dominant role compared to social factors in shaping students' learning interest. Therefore, proper management of social media use is necessary to support students’ academic engagement.